2000
DOI: 10.1111/j.1365-2621.2000.tb13593.x
|View full text |Cite
|
Sign up to set email alerts
|

Headspace Evaluation of Methanethiol and Dimethyl Trisulfide in Aqueous Solutions of Soy‐protein Isolates

Abstract: Volatile compounds from 2 samples of aqueous soy-protein isolates (SPI) (7%) were analyzed using both static and dynamic headspace methods. Based on dynamic headspace analyses, the most powerful odorants were (1) dimethyl trisulfide, (2) methanethiol, (3) hexanal, (4) an unidentified charred, sweaty feet-like odor, (5) 2-pentyl furan, (6) 2,3-butadione, and (7) an unknown burnt-like odor. The most powerful odorants by static headspace analyses were (1) dimethyl trisulfide, (2) hexanal, (3) methanethiol, and (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 15 publications
3
29
0
Order By: Relevance
“…There was no significant difference in the chromatograms obtained at the 3 temperatures, suggesting that there is little if any thermal conversion of the sulfur volatiles in the GC injector. This conclusion agrees with the study of Boatright and Lei (2000). They evaluated methanethiol and dimethyl trisulfide in soy protein isolates using GCO/MS with GC injector temperatures of 130 °C and 210 °C.…”
Section: Possible Injector Artifactssupporting
confidence: 88%
“…There was no significant difference in the chromatograms obtained at the 3 temperatures, suggesting that there is little if any thermal conversion of the sulfur volatiles in the GC injector. This conclusion agrees with the study of Boatright and Lei (2000). They evaluated methanethiol and dimethyl trisulfide in soy protein isolates using GCO/MS with GC injector temperatures of 130 °C and 210 °C.…”
Section: Possible Injector Artifactssupporting
confidence: 88%
“…We also compared the minimum level of methanethiol detectable by GCO and found that we could clearly detect 0.08 ng at the sniff port and 0.04 ng was not clearly detectable. Determinations of the minimum quantity necessary to detect these compounds by olfactometry was accomplished by the same two investigators that performed the olfactometry analyses in our previous investigations (18,29). By using 0.058 mg/m 3 as the odor threshold for hexanal, the calculated odor threshold for methanethiol using this method is 0.0014 mg/m 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In a previous investigation (18), GCO was used to identify major odorants from the headspace of aqueous solutions of soy protein isolates (SPI) using both static and dynamic headspace methods. Based on dynamic headspace analyses, the most powerful odorants were (i) dimethyl trisulfide (DMTS), (ii) methanethiol, (iii) hexanal, (iv) an unidentified charred sweaty feet-like odor, (v) 2-pentyl furan, (vi) 2,3-butadione, and (vii) an unknown burnt-like odor.…”
mentioning
confidence: 99%
“…With its low odour threshold of 0.008 ppb in water (Milo & Grosch, 1996), dimethyl trisulfide is suggested to play an important part as key aroma compound in lupin protein extracts. Boatright and Lei (2000) found methanethiol as possible precursor of dimethyl trisulfide in the headspace of soy protein extracts.…”
Section: Fatty Acidmentioning
confidence: 98%